Work/family life by 2040: Between a gig economy and traditional roles. (May 2020) - Benavides Rincón, Guillermina; Montes Martínez, Yolanda
Highlights: The incorporation of mothers into the labor market affected the work/life balance for women and men. Family structure is changing but the institutions around it have remained the same. Work/life balance is a social conflict affecting women and men that needs practical measures to achieve a better family dynamic. The future of family structures and the future of the labor market are the key uncertainties to visualize futures scenarios. Abstract: This research envisions four future scenarios of work/life balance for Mexican families by 2040. The incorporation of mothers into the labor market mainly affected the work/life balance of women, but the research concludes that this issue is not unique to only women. Twenty semistructured interviews were conducted with families, including both men and women experiencing this conflict, and a trend analysis was performed to identify the main drivers of change that can affect the work/life balance of families. The analysis identified two critical uncertainties for constructing a scenario matrix using the deductive intuitive logic approach. The results show that the current economic reality forces household members, including both males and females, to adapt the family structure and dynamic to work needs. This transformation of middle-class families shows the need to identify the issue as a gender-neutral social conflict to define actions that reduce work pressures and achieve a family dynamic allowing a better work/life balance for the entire family and not only for women.